2020
DOI: 10.1101/2020.04.26.20079244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of COVID-19 virus infection in Guilan province, Iran

Abstract: Background: The extent of infection by coronavirus disease 2019 has not been well known. In this study we aimed to determine seropositivity of COVID-19 virus infection in population of a highly affected area in north of Iran. Methods:In a population-based cluster random sampling design through phone call invitation, a total of 196 household including 551 subjects agreed to participate in this study. Each participant were taken 50ml blood sample at health care center. Rapid test kits were used to detect antibod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
139
7
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(158 citation statements)
references
References 18 publications
10
139
7
2
Order By: Relevance
“…A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]23,28,39 and 1 was uncertain quality. 7,37…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]23,28,39 and 1 was uncertain quality. 7,37…”
Section: Resultsmentioning
confidence: 99%
“…Data from prevalence studies for children and adolescents compared with adults are shown in Figure 4. 7, [32][33][34][35][36][38][39][40][41][42][43][44][45] We did not undertake a meta-analysis of population screening studies given the important differences in the populations, epidemic time points, and methodologies involved.…”
Section: Population Screening Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest proportion of participants who tested positive for IgG titers amongst studies reporting an aggregate IgG seropositivity rate was 21.0% in a representative, general population study with 528 participants from the Guilan Province in Iran. (16) Of the 11 (41%) studies that reported the proportion of study participants that tested positive for IgM SARS-CoV-2 titers, the reported proportions ranged from 0.6% in a study of 1,000 blood donors in Scotland(13) to 32.0% in a study with a non-representative, general population sample of 200 participants from Chelsea, Massachusetts in the United States. (17) The studies on the ends of this range reported aggregate proportions of patients who tested positive for IgG titers, IgM titers, or both titers rather than separately.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…(18) The highest proportion of study participants that tested positive for IgM titers amongst studies reporting IgM speci cally was from a representative sample of the general population containing 528 participants in the Guilan Province in Iran (18.9%). (16) One study (4%) evaluated neutralizing antibodies and detected these antibodies in 1% (5/500) of the study sample. (13)…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%